PRACTICAL APPROACH AS AN IMPORTANT SPECIFICATION OF TEACHING ENGLISH IN MEDICAL UNIVERSITIES - Buranova, Dilafruz (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The study examines a practical approach to teaching medical English as an essential element in teaching methodology. The main goals of a practice-oriented approach in teaching English to medical students are noted. The study aims to identify the didactic aspects of the practical approach, which implies the formation of linguistic competence through professional activity. The tasks of applying both linguistic and professional knowledge while developing the ability to effectively use English in medical practice are analyzed. Research methods involve the introduction of theoretical knowledge into practice, the construction of study with a contextual approach and practical application of language skills, and the integration of linguistic and professional knowledge. English teaching programs in medical high schools require ensuring proportionality between medical disciplines and English. The results of the study confirm that a practical approach to mastering English in medical universities, which is based on ESP, is a comprehensive approach that allows students to increase their cognitive language activity. The study proposes the key methodological aspects of systematic modeling of educational and methodological support with the integration of knowledge from various medical disciplines. It presents the principles and factors of effective use of the English language in a medical context with the support of professional skills.
Keywords: English; medical specialty; practice; methodology; medical students; contextualization; ESP